Analysis Acceptance of LinkedIn Application Users Using the Revised Technology Acceptance Model for Social Media and Information System Success Model - Bagas Mahardika; Anggy Trisnawan Putra (Journal of Advances in Information Systems and Technology, 2024)
Social media is a web-based application that provides facilities for communicating and chatting online, sharing videos and images, carrying out activities related to education and business, making learning easier, searching for information, and looking for work. LinkedIn is a social media designed to help many people make connections in business, share experiences, and find work. So far, LinkedIn is the most popular social network when it comes to recruiting. More than 95% of recruiters use social media in their recruiting process, which indicates that they use LinkedIn. The aim of this research is to determine the factors that influence perceived usefulness, perceived ease of use, and intention to use by using a combination of the revised Technology Acceptance Model (TAM) for social media and the Information System Success Model (ISSM) methods. This research uses a quantitative approach with sample criteria, namely people from Central Java who have used LinkedIn to look for work and are aged between 19 – 34 years. This research obtained 140 valid data through surveys distributed via social media. The results obtained found influencing factors. The results of the hypothesis test showed that there were 10 hypotheses that were accepted. From this hypothesis, there are several factors that influence perceived usefulness, namely information quality, service quality, critical mass, perceived playfulness, and trustworthiness. Then the factors that influence perceived ease of use are system quality and service quality. Then the factors that influence intention to use are information quality, trustworthiness, perceived usefulness, and perceived ease of use.